Transesterification Of Kesambi Seed Oil (Schleichera oleosa L) With Zinc Oxide (ZnO) Catalyst And Buffered Multi-Walled Carbon Nanotubes (MWCNTs) - Nikmatin - Chasanah; N P Asri (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
The alternative energy that has been developed today, one of which is biodiesel, biodiesel is the fuel process of an updated source. One of them utilizes kesambi seed oil as a raw material for making, this is done because of the many results of the kesambi tree in Indonesia so that it has great potential as a biodiesel raw material. This research focuses on the development of the ZnO catalyst with MWCNTS as a buffer for the transesterification of Kesambi seed oil. The purpose of this research is to study the type of impregnation time, sulfonation time And the appointer is stirring during the transesterification process on product yield results. Catalyst is characterized by X-Ray Diffraction Analysis Test (X-RD, Brunauer Emmett-Teller (BET), Scanning Electron Microscopy Energy Dispersive X-Ray Spectroscopy (SEM-EDX), and Fourier Transform Spectroscopy Infra-Red (FTIR). The results showed the highest yield of 85.46% obtained at a variable of 12-hour impregnation time, with a 4-hour sulfonation time with a temperature of calcination of 500 ° C, the calcination time of 4 hours, the molar ratio of oil against methanol 1 15, the transesterification reaction temperature was 65 ° C, and time under 7-hour transesterification reactions.